Models of information conflicts in infocommunication systems - Bezvershenko, E.I.; Huzii, M.M. (Problems of Informatization and Management, 2023)
In the present study, a systematic analysis of models of information conflict interaction in infocommunication systems (ICS) is carried out. The infrastructure of ICS is realized by a set of telecommunication and information-computing systems (TCS/ICS). The analysis of scientific publications shows the relevance of the problem of improving existing and developing new methods of managing information security processes in the dynamic conditions of information confrontation, taking into account the uncertainty of information about the enemy’s actions, the need to develop theoretical foundations, scientific methods and models of information security management in IIS. At the present stage, several approaches to modeling information conflicts coexist, which reproduce the specific features of the conflict component. They can be conditionally divided into approaches based on precise description and approaches based on product or game models. The mathematical model of the dynamics of information conflict in TCS/IS is represented by a well-known system of randomized equations for the dynamic change in the probabilities of states of conflicting systems. An important feature of the information conflict is the uncertainty of the use of the allocated resource by the operating systems. The methodology and stages of studying the interaction of secure information systems operating in the environment of information conflict in TCS/IOS are determined.